The Level Of Achievement Of Lean Manufacturing Implementation Status Before And After The Development Of KPI's At An Aerospace Manufacturing Company - Mohamad, Effendi; Abdullah, Rohana; Wan Mahmood, Wan Hasrulnizzam (2004)
This research study focuses on the issue of the level of achievement of Lean Manufacturing Implementation status before and after the development of Key Performance Indicators (KPIs) at an aerospace manufacturing company. The KPIs are targeted to provide this company with a good performance measurement tools in supporting the success of their Lean manufacturing journey. The assessment will be based on Red Amber Green (RAG) status. KPIs development in this research can improve of productivity and efficiency in manufacturing engineering system.